Global Diversification in Medicine Regulation: Insights from Regenerative Stem Cell Medicine. (3rd April 2019) - Rosemann, Achim; Vasen, Federico; Bortz, Gabriela
ABSTRACT: Medicine regulation worldwide has undergone a process of regulatory diversification. The evidence-based medicine (EBM) paradigm, centered on multi-phase randomized controlled trials, is increasingly contested and replaced by new models of clinical validation. To explain these changes, STS research has cited just a few factors, e.g. growing pressure form health consumers; the role of pharmaceutical companies to lobby for fast, affordable drug development; the influence of neoliberal ideas and libertarian advocacy of deregulation; and the agency of national governments to enable domestic innovation opportunities in the context of global competition and inequalities. Those factors individually cannot account for the increasing variation in medicine regulation at both national and global levels. Instead it is helpful to integrate elements of existing explanations into a framework with four pairs of conflicting regulatory choices, which play a central role in the formation of medicine regulation. We use this framework to compare regulatory changes in the USA, European Union, China, India, Argentina, and Japan. Across these jurisdictions, the case studies illustrate four dynamics of diversification. Key regulatory concepts such as evidence, risk, safety, efficacy, responsibility and accountability acquire different meanings, reshaping medicine innovation in far-reaching and often contradictory ways. The boundaries between medical research and healthcare provision, commerce and humanitarian service, as well as state control and medical self-regulation are re-defined.